STUDY OF THE FREQUENCY RESPONSE OF CONCRETE SPECIMENS IN DIFFERENT STRENGTH CLASSES - Lima, Cássio Humberto (Seven Editora, 2025)
Concrete, being a heterogeneous composite material sensitive to the proportions of its constituents, exhibits significant variations in its mechanical and dynamic behavior. This study analyzed the vibrational behavior of concrete specimens with four compressive strength classes (15, 20, 25, and 30 MPa) through experimental modal analysis and determination of Frequency Response Functions (FRF). For each class, 10 specimens were molded in plywood forms using Portland cement CP II, quartz sand, granite aggregate, and water in specific volumetric proportions, followed by curing for 28 days. Impulsive excitation was applied with an instrumented hammer, and acceleration responses were acquired using a dedicated acquisition system in the 0 to 2560 Hz range, with evaluation of the coherence between excitation and response for FRF validation. The curves obtained showed a systematic shift of resonance peaks to higher frequencies as compressive strength increases, in addition to more sTable spectral responses in the higher classes, highlighting the strong correlation between dynamic stiffness and mechanical strength. The methodology employed confirmed the potential of modal analysis as a sensitive non-destructive technique for characterizing the vibrational response of concrete, providing relevant information for applications in quality control and evaluation of structures subjected to dynamic actions.DOI: https://doi.org/10.56238/sevened2025.036-096